Prevalencia de mastitis en vacas lecheras lactantes en el municipio de San Pedro de los Milagros, Antioquia (2001)
ABSTRACT: A field study was conducted from July to September 1999 to determine the prevalence of bovine mastitis in a Colombian country Municipality named San Pedro de los Milagros. To measure the mastitis prevalence it was used the Californian mastitis test (CMT). Animals sampled were 112 lactat ing cows, randomly chosen out from 15 different rural zones. The teats showing suspicious results were resampled and taken to a microbiological lab in order to cultivate them. A cellular counting, culture and antibiogram was carried out to the samples. Obtained data are presented in descriptive form. It was also carried out the chi square statistical test to measure the association degree of some variables. Mastitis prevalence per quarter in the municipality was 12,3 % (55 quarters with results equal or bigger than suspicious). Among the affected quarters of the total sampled, The result of the CMT more frequently found was two crosses (4,4 %). The more frequently bacteria isolated was Streptococcus agalactiae, followed by coagulase negative Staphylococci and Staphylococcus aureus with 47 %, 14,6 % and 13 % respectively. In the antibiogram carried out it was found that from the total of Streptococcus agalactiae positive samples, 19,3 % showed penicillin resistance. It can be concluded that mastitis prevalence per quarter in the area is not very high, keeping in mind that an important percentage of producers do not fulfill the minimum hygienic milking procedures. 57,1 % of the producers do not wash and dry the udder and 42,9 % don’t make postmilking teat dipping. It can also be concluded that the bacterial species founded is the more frequently reported in other works carried out in our country. It is important to underline the progressive Streptococcus agalactiae penicillin resistance. It is well known that Streptococcus agalactiae has been controlled in other countries with this antibiotic. Resistance can be due to indiscriminate use of antibiotics for treating diverse problems in bovine without the prescription of a Veterinarian.